Systematic framework for sustainability assessment on chemical production pathway: basic engineering stage - Liew, W. H. (Institution of Chemical Engineers, 2016)
Assessment on sustainability of production pathway is an important step to promote the sustainability features during early process design. The early process design can be divided into three stages, which are research and development (R&D), preliminary engineering and basic engineering. Note that, the assessment frameworks for R&D and preliminary engineering stages have been presented in our previous works. As continuation, a systematic framework for the assessment of chemical production pathway in basic engineering design stage is presented in this work (Liew et al., 2014b, 2015). This framework emphasises on the inherent safety, health and environment (SHE) and economic performance (EP) assessment of chemical production pathway, with the integration of fuzzy optimisation approach as the multi-objective analysis tool. Following the proposed assessment framework, selection of pipe size and types of fittings is considered in this framework for improvement of inherent SHE and EP, as those selection criteria are the key design parameters at this design stage. To illustrate the application of the proposed framework, a case study on biodiesel production pathway assessment is presented.